Community Monitoring: Promoting Conservation in Candelaria, Campeche, Mexico (Agro Productividad, 2025)
Objective: To engage agricultural producers in the implementation of a community-based wildlife monitoring system aimed at generating citizen science. Design/Methodology/Approach: Community monitors were trained in bird observation and identification techniques, as well as in the operation and management of camera traps. Photographic trapping stations were installed adjacent to milpas to identify the wildlife species frequenting these agroecosystems. Results: Eight local individuals were trained as community monitors. Over 811 trap-nights, a total of 32 species were identified, eight of which are listed under some category of protection. The species with the highest number of records are classified as generalists. Most of the recorded species exhibit nocturnal or crepuscular activity patterns. The data confirm the effectiveness of photographic trapping as a method for detecting wildlife species in milpa systems.Study Limitations/Implications: The communities involved in the study are located in remote areas without access to the electrical grid and are characterized by irregular land tenure conditions, factors that contribute to social distrust and certain levels of community apathy.Findings/Conclusions: A high diversity of species interacting with milpa systems was observed. The photographic trapping method proved effective for wildlife detection in milpas in Campeche and successfully facilitated the integration of local participants as community monitors.